Follow-up of Toxoplasmosis during Pregnancy: Ten-Year Experience in a University Hospital in Southern Brazil - Amanda Andrade Diesel; Suzana de Azevedo Zachia; Ana Lúcia Letti Müller; Amanda Vilaverde Perez; Flavio Antonio de Freitas Uberti; José Antônio de Azevedo Magalhães (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective To describe a population of pregnant women diagnosed with toxoplasmosis and their respective newborns, describing the hospital protocol for treatment and follow-up. Methods Retrospective cohort of pregnant women with acute toxoplasmosis infection and risk of transplacental transmission who were sent to the Fetal Medicine Group of Hospital de Clínicas de Porto Alegre (HCPA) between - January 1, 2006 and December 31, 2016. All patients with confirmed disease were included. The diagnostic protocol and treatment were applied; a polymerase chain reaction (PCR) analysis of the amniotic fluid was used to diagnose toxoplasmosis and determine the treatment. The newborns were followed up at the pediatric outpatient clinic specializing in congenital infection. The patients who were not followed up or were not born in the HCPA were excluded. Results A total of 65 patients were confirmed to have gestational toxoplasmosis; 40 performed amniocentesis, and 6 (15%) were identified as having positive PCR in the amniotic fluid. In five of those cases, this result associated with the gestational age defined the triple therapy during pregnancy, and in one case, it defined the monotherapy (advanced gestational age). A total of 4 of these newborns were treated from birth with triple therapy for 10months, 1 was not treated (due to maternal refusal), and 1 progressed to death within the first 54 hours of life due to complications of congenital toxoplasmosis. Of the 34 remaining cases with a negative PCR, 33 were treated with monotherapy and 1 was treated with triple therapy (ultrasound findings); of these children, 9 (26.5%) presented negative immunoglobulin G (IgG), 24 (70.6%) presented positive IgG (but none presented positive immunoglobulin M [IgM]), and 1 (2,9%) presented alterations compatible with congenital disease and started treatment with the triple therapy soon after birth. Out of the total sample of 60 patients, among the 25 who did not perform amniotic fluid PCR, 5 were treated with triple therapy (ultrasound findings/prior treatment) and 20 patients were submitted to monotherapy; only two newborns underwent treatment for congenital toxoplasmosis. Among the 65 cases of gestational toxoplasmosis, 6 (9,2%) children had a diagnosis of congenital toxoplasmosis, and 2 patients with triple therapy felt severe adverse effects of the medications. Conclusions The present study suggests that research on PCR screening of the amniotic fluid may be useful to identify patients with a higher potential for fetal complications, who may benefit from the poly-antimicrobial treatment. Patients with negative PCR results must continue to prevent fetal infection with monotherapy, without risk of fetal or maternal impairment.